Smooth Muscle Differentiation of Penile Stem/Progenitor Cells Induced by Microenergy Acoustic Pulses In Vitro. Issue 12 (1st October 2019) - Peng, Dongyi; Yuan, Huixing; Liu, Tianshu; Wang, Tianyu; Reed-Maldonado, Amanda B.; Kang, Ning; Banie, Lia; Wang, Guifang; Tang, Yuxin; He, Leye; Lin, Guiting; Lue, Tom F.
Abstract: Introduction: Modulating tissue-resident stem and progenitor cells with a non-invasive, mechanobiological intervention is an optimal approach for tissue regeneration. Stem cell antigen-1 (Sca-1) has been identified as a stem cell marker within many organs but never within the penis. Aim: To localize and isolate penile stem/progenitor cells (PSPCs) and to evaluate cellular differentiation after exposure to induction medium and microenergy acoustic pulse (MAP) therapy. Methods: Six male Sprague-Dawley rats were used to isolate PSPCs. Isolation was followed by stem cell characterization and differentiation assays. The PSPCs were then treated with MAP (0.033 mJ/mm 2, 1 Hz) at various dosages (25, 50, 100, and 200 pulses) and for different durations (1, 2, 4, 6, or 8 hours) in vitro. Main Outcome Measure: The PSPCs (Sca-1-positive cells) were isolated using the magnetic-activated cell sorting system. PSPC cellular differentiation was assessed after induction with induction medium and with MAP in vitro. Wnt/β-catenin signaling was also assayed. Results: The PSPCs were successfully localized within the penile subtunic and perisinusoidal spaces, and they were successfully isolated using magnetic-activated cell sorting. The stemness of the cells was confirmed by stem cell marker characterization and by multiple differentiation into smooth muscle cells, endothelial cells, adipocytes, and neurons. MAP-induced PSPCs differentiated into smooth muscle cells by activating the Wnt/β-catenin signaling pathway in a time- and dosage-dependent manner. Clinical Implications: By modulating resident PSPCs, MAP may have utility in the treatment of erectile dysfunction (ED). Strengths & Limitations: This study provides solid evidence in support of microenergy therapies, including both MAP and low-intensity extracorporeal shock wave therapy, for the treatment of ED. Additional studies are needed and should include additional stem cells markers. Furthermore, studies exploring the underling mechanisms for PSPC activation and differentiation are required. Conclusion: PSPCs were successfully identified, localized, and isolated. Additionally, MAP provoked PSPCs to differentiate into smooth muscle cells via the Wnt/β-catenin signaling pathway. As such, MAP provides a novel method for activating endogenous tissue-resident stem/progenitor cells and might facilitate stem cell regenerative therapy targeting ED.